Marine Environmental Change Induced by Anthropogenic Activities – From a Viewpoint of Aquatic Palynomorph Assemblages Preserved in Sediment Cores of Beppu Bay, West Japan - Matsuoka, Kazumi; Kojima, Natsuhiko; Kuwae, Michinobu (Frontiers in Marine Science, 2022)
Stratigraphic cluster analysis using aquatic palynomorphs preserved in the core sediments revealed a rapid eutrophication due to anthropogenic activities from the mid 1960s in Beppu Bay, East Kyushu, Japan. These assemblages were divided into three major units: BP-I, BP-II and BP-III, and also only dinoflagellate cyst assemblages were divided into the following four units in Beppu Bay: BP-A, BP-B, BP-C, and BP-D. Unit boundaries based on aquatic palynomorphs and dinoflagellate cysts were different except in the upper part, BP-III and BP-D, both of which clearly indicated anthropogenic eutrophication in both sea water and bottom sediments. On the other hand, in dinoflagellate cyst assemblages, Unit BP-A was characterized by stable occurrence of Spiniferites bulloideus and Spiniferites hyperacanthus, Lingulodinium machaerophorum of Gonyaulacales, and reduction of heterotrophic Peridinioid Brigantedinium spp. In Unit BP-C there was a clear decrease of L. machaerophorum. Unit BP-B was characterized by decreases of S. bulloideus, S. hyperacanthus, and L. machaerophorum, and little increase of Spniferites bentori. Unit BP-C was characterized by an increase in S. bulloideus and heterotrophic Peridinioid Echinidinium spp. Unit BP-D was subdivided into Subunit BP-D1 where dinoflagellate cysts showed a marked increase in S. bulloideus accompanied by the appearance of L. machaerophorum and Tuberculodinium vancampoae, and Subunit PB-D2 where there was a decrease of total dinoflagellate cysts. From the dinoflagellate cyst assemblages, the marine environment of the period of BP-A Unit was suggested to be warm and stable. However, L. machaerophorum started to decrease in BP-B. The clear decrease of L. machaerophorum suggest that the marine environment became cooler than that of Unit BP-A. Significant increases of S. bulloideus, S. hypearcanthus, L. machaerophorum, T. vancampoae, Brigantedinium spp., and Polykrikos kofoidii were characteristic of Unit BP-D. The increase in total dinoflagellate cyst density and the increase of the ratio of heterotrophic dinoflagellate cysts in Subunit BP-D1 are manifestations of the Oslo fjord Signal and Heterotroph Signal, respectively. In addition, the decrease in microforaminiferal lining that continued from Unit BP-C to Unit BP-D might indicate deterioration of the bottom sediment environment.